1945
DOI: 10.2118/945034-g
|View full text |Cite
|
Sign up to set email alerts
|

Average Permeabilities of Heterogeneous Oil Sands

Abstract: THIS paper discusses the practical problem of estimating a single equivalent permeability for an oil reservoir, or a portion thereof, whose actual permeability varies in an irregular manner. Limiting averages for general types of permeability. variation are developed, and illustrated by examples involving important, specific types of variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 0 publications
1
107
0
1
Order By: Relevance
“…Moreover, even if the nature of these variations were known, the difficulties of exact analytical treatment would still force the use of averaging procedure and reduction to an equivalent permeability system." He then goes on to mention the Cardwell and Parsons (1945) bounds for averaging, and treats some special cases where simple geometric trends in permeability are known.…”
Section: The Early Approachmentioning
confidence: 99%
“…Moreover, even if the nature of these variations were known, the difficulties of exact analytical treatment would still force the use of averaging procedure and reduction to an equivalent permeability system." He then goes on to mention the Cardwell and Parsons (1945) bounds for averaging, and treats some special cases where simple geometric trends in permeability are known.…”
Section: The Early Approachmentioning
confidence: 99%
“…Field dykes were observed to be relatively homogeneous due to an equal fracture density in its parallel and perpendicular directions, suggesting a K of 5 × 10 −9 m s −1 , while the sandstone value from the literature is well established at 1.2 × 10 −5 m s −1 . Those permeability values were upscaled to a regional scale using the model defined for banded structures by Cardwell and Parsons (1945). This model suggests that equivalent K for groundwater flow parallel and perpendicular to the banded heterogeneity trend is defined as the arithmetic (μ a ) and harmonic (μ h ) mean of individual units of K, respectively.…”
Section: Previous Hydrogeological Model Of the Lagan Valley Aquifermentioning
confidence: 99%
“…Simple averaging techniques are local methods and assume that KV depends only on the Kf values within the block (Cardwell & Parsons, 1945;Matheron, 1967). For a perfectly layered soil, it can be shown that KV is equal to the harmonic mean (Kh) of the cell conductivities inside the block when the flow is perpendicular to the layers, and to the arithmetic mean (Ka) when the flow is parallel to the them .…”
Section: Hydraulic Conductivity Upscaling Methodsmentioning
confidence: 99%
“…It is well established that KV must be between the arithmetic mean and the harmonic mean (Cardwell & Parsons, 1945). The p-norm average was proposed as a flexible easy-to-compute alternative since it can provide a value for KV between those two limits as a function of the exponent p (A. :…”
Section: Hydraulic Conductivity Upscaling Methodsmentioning
confidence: 99%
See 1 more Smart Citation